Photovoltaic grid-connected with transformer less renewable source system with multilevel NPC inverter. (19th March 2020) - Yadav, Anchal; Tiwari, Pratibha
In research used permanent magnet synchronous generator. Ac grid linked by wind energy with a load. The loads in a grid might be harmful to nature. Hence, the injection of unbalance current into renewable grid should be avoided since these Negative sequence currents and harmonic currents will cause an unwanted improvement of the current line. Dealing with problems is to use effective controllers with multilevel inverters. A multilevel inverter handed down to improve THD. In this case, a nine-level and an eleven-level inverter are used for the set the values of voltage increment and THD decrease with 12.87% to 4.38%. Powers is a limitation of stabilisation of DC and the power of reactive is close to unity. Low capacitors filter to eradicate the harmonics presence in the system. For the performance evaluation of the approaching for a modelling of the AC grid, nonlinear load, multilevel inverter and renewable energy resources (e.g., wind power generation) was developed in a MATLAB/SIMULINK environment.